Fabrication and characterisation of NiFe nanoparticles and nanowires. - Renuka Prasobhan. (2012)
Nanoparticles are widely researched upon mainly for its capability and potentials in biomedical applications, such as cancer therapy and as contrast agents in Magnetic Resonance Imaging (MRI). Thus far, iron oxide nanoparticles are considered one of the most appropriate for these applications, due to its paramagnetic nature. But it hardly offers flexibility in manipulating its magnetic properties in order to serve its purposes.